The Relationship Between Students' Perceptions of Geography Teachers' Pedagogical Competence and the Learning Outcomes of Grade X Students at Palu State Senior High School 9 - Nabila, Putri; Nurvita, Nurvita; Hamid, Abdul; Durrotunnisa, Durrotunnisa (Journal of Educational Sciences, 2025)
Education is a human endeavor to nurture and develop innate physical and spiritual potential. This study aims to determine students' perceptions of geography teachers' pedagogical competence, assess student learning outcomes, and analyze whether there is a relationship between students' perceptions of geography teachers' pedagogical competence and the learning outcomes of 10th grade students at SMA Negeri 9 Palu. The type of research used was descriptive-correlational research with a quantitative approach. Student learning outcomes were classified as very good, with an average score of 84.27 and the majority of students obtaining scores in the range of 81–85 (40%), although none achieved scores above 90. There is a very strong relationship between students' perceptions of geography teachers' pedagogical competence and the learning outcomes of 10th grade students, as evidenced by a correlation coefficient of 0.907 and an influence contribution of 82.2%. This means that the better the students' perception of the teachers' pedagogical competence, the higher the learning outcomes achieved. Thus, this study confirms that the mastery of teachers' pedagogical competence plays an important role in improving the quality of student learning outcomes at SMA Negeri 9 Palu.